Analysis on the innovation efficiency of China's electronic and communication equipment industry. Issue 1 (March 2022) - Wang, Yu; Li, Junwei; Zhong, Shen
Abstract: The development of electronic and communication equipment industry is the driving force of economic growth, and innovation is the basic motivation for the development of electronic and communication equipment industry. The evaluation of innovation efficiency of electronic and communication equipment industry (IEEC) is conducive to economic growth and better development of electronic and communication equipment manufacturing industry. The existing researches mainly focus on the efficiency evaluation of high-tech industry, and there is few study on the IEEC. To fill the gap, based on DDF model and Global-Malmquist index, this paper estimates the IEEC in 20 provinces of China from 2009 to 2018. The results show that: (1) From the perspective of time dimension, China's IEEC shows an overall growth trend in the past decade from 2009 to 2018. (2) From the regional perspective, IEEC exists differences among regions. Under the meta-frontier and group frontier, the value of IEEC in the central region is higher than the value of IEEC in the eastern region and western region. (3) From the decomposition index, the growth of IEEC depends more on technological progress, rather than efficiency improvement. Combined with the above conclusions, some policy implications are proposed.